Digital Divide for Persons with Disabilities Related to Indonesian Information Technology Accessibility from Legal Perspective - Nurhayati, Siti; Kardi, Kardi (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
Website accessibility and digital content for people with disabilities in Indonesia remain inadequate. Based on the Internet Inclusive Index, Indonesia ranks 66th out of 120 countries with a score of 69.75 and fails to meet the Web Content Accessibility Guidelines (WCAG). Despite the enactment of Law Number 8 of 2016 concerning Persons with Disabilities and the ratification of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) in 2011, accessibility rights to information and communication technology have not been fully realised. Existing studies have yet to comprehensively examine how digital law can be effectively applied to close the gap between legal norms and the digital inclusion of persons with disabilities. This research fills that gap by analysing the intersection of disability rights and digital law, identifying key legal and sociocultural barriers that contribute to the digital divide. Employing normative juridical methods and a statutory approach, the study is analysed using qualitative descriptive techniques. The digital divide is found to stem from three main factors: legal substance, institutional structures, and societal culture. The novelty of this research lies in its use of digital law as a conceptual and regulatory framework to formulate inclusive digital policy recommendations. These include the strategic implementation of Articles 5 and 127 of Law No. 8 of 2016, as well as the proposal for a government-regulated digital portal based on universal design principles. Additionally, a cultural shift from a compassion-based to a rights-based approach is essential to ensure that persons with disabilities are recognised as equal participants in the digital society.